METHOD FOR PRODUCING A POLYMETHYL METHACRYLATE BONE CEMENT, BONE CEMENT KIT FOR USE IN SUCH A METHOD AND BONE CEMENT MANUFACTURED ACCORDING TO SUCH A METHOD - THOMAS KLUGE; SEBASTIAN VOGT (2018)
A subject matter of the invention is a polymethylmethacrylate bone cement. The method comprises the steps of providing a cement powder that contains at least one particulate polymethylmethacrylate orpolymethylmethacrylate-copolymer of the sieved fraction of less than 100 um, one initiator, and at least one particulate or fi brous additive that is insoluble in methylmethacrylate, whereby the additive has an absorption capacity at room temperature of more than or equal to 0.6 g methyl methacrylate per gram of additive; and of providing a monomer solution that con tains at least one methylmethacrylate and one activator, and contacting the cement powder and the monomer solution, whereby the mixing takes place without the ap plication of shearing forces. The invention also relates to a bone cement kit for use in said method and bone cement that can be produced through said method. 本发明的主题是聚甲基丙烯酸甲酯骨胶泥。此方法包括以下步骤：提供胶泥粉末，其含有至少种具有筛分级分小于100μm的颗粒聚甲基丙烯酸甲酯或聚甲基丙烯酸甲酯共聚物，种引发剂，和至少种不溶于甲基丙烯酸甲酯的颗粒或纤维状的添加剂，其中添加剂具有在室温下的吸收容量为大于或等于0.6